Synthetic biology – pathways to commercialisation. Issue 1 (18th March 2019) - Clarke, Lionel J.
Abstract : Synthetic biology is transforming the ability to manufacture increasingly needed bio‐based products in response to rising market demand. By applying engineering principles to the convolution of recent advances in genomic engineering techniques, information technology and automation, synthetic biology is facilitating the replacement of time‐consuming 'discover and grow' approaches by more precise and affordable 'biodesign and biomanufacture' processes. Meantime, societal awareness of specific health, well‐being, and environmental issues is increasing 'market pull' that will shape future pathways to commercialisation. Market interests will not only shape targets for product function and cost but also increasingly question their provenance. Sustainability concerns are already driving demand to replace petrochemical‐derived by bio‐derived products, but many established industries wishing to transition may lack familiarity with bio‐manufacturing processes and with the wider issues associated with large‐scale bio‐feedstock supply chains. Meantime, commercialisation of synthetic biology today is being advanced mostly via start‐ups and SMEs. Combining the knowledge and skills required to respond to market interests, as the scale of operations and complexity of issues expands, is likely to stimulate an increasing diversity of collaborative approaches.